Development and Effect of a Participatory Moral Education Programme on Pre-Service Teachers’ knowledge of and Attitude to Moral Concepts in Social Studies (2012)
Social Studies as a subject is meant to involve pupils in meaningful learning activities to develop good citizenship and attitude to make informed decision on social matter. However, literature abounds that Social Studies is taught in schools using lecture methods which do not promote values and rational habits. This could be attributed to the fact that few studies have been carried out in the area of training of teachers to develop moral education programme. One of the ways by which students could be involved in meaningful learning as well as develop right affective domain is to integrate moral education programme into the learning process. This study, therefore, developed a moral education programme and determined its effect through the participatory approach on pre-service teachers‟ knowledge of and attitudes to moral issues in Nigerian colleges of education. The methodology is in two parts: first the study adopted the participatory approach to develop the moral education programme using Roberts programme development model; and secondly the efficacy of the programme was determined using the pretest- posttest, control group, quasi-experimental design with a 2x2x2 factorial matrix used. Intact classes made up of 308 female, and 160 male pre-service teachers from four colleges of education in Osun, Oyo, Ondo and Lagos states participated in the study. The instruments used were: Moral Knowledge Test (r = 0.78), Moral Attitude Scale (r = 0.85), Participatory Moral Education Programme for experimental group and Modified Conventional Learning Guide for the control group. The treatment lasted for ten weeks. Seven null hypotheses were tested at 0.05 level of significance. Data were subjected to descriptive statistics and analysis of covariance. The development of the moral education programme which involves, workshop, focus group discussion, presentation of posters, moral club by the pre-service teachers allows the enhancement of right conduct, honesty, fairness and skills of collaborative and broad team group activities. There was a significant main effect of treatment on pre-service teachers‟ knowledge of moral education (F(2,465)= 58.24, p <.05) and attitude (F(2,465) = 20.32, p < .05) Participants in the participatory group had higher knowledge mean score (x =10.63) than those in the modified conventional method (x = 8.76). Religion has significant effect on post-test knowledge scores of pre-service teachers‟ (F(2.465) = 17,29, p < .05), and attitude (F (2,465) = 3.70, p < .05). There is no significant effect of gender on pre service teachers‟ knowledge and attitude. However, female students had higher adjusted post-test mean knowledge score (x = 9.70) than the male students (x= 9.66). The participatory approach enabled the pre-service teachers to live in peace and relate better with others regardless of tribe, sex and religion. Participatory Moral Education Programme enhanced both the knowledge and also influence attitudes of Pre-service teachers in moral concepts in Social Studies. It is therefore, recommended that the participatory moral education programme should be used in social studies classrooms by all teachers because it is capable of improving learners‟ knowledge and attitude to moral issues.